Investigation of flow around flexible bodies - Lee, Yuan Long (2016)
Renewable and clean energy have an added significance today. However, existing renewable and clean energy have their limitations. Among the various renewable and clean energy, the focus of this final year project is on hydro-kinetic energy. As such, this project aims to investigate the effect of vortex shedding as a potential source of hydro-kinetic energy that has minimal impact on marine life and the environment. Hydro-kinetic energy generated by vortex shedding is then harvested by converting it to electrical energy for use.